2021
DOI: 10.1038/s41398-021-01418-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing olfactory, memory, social and circadian phenotypes associated with schizophrenia in a genetic model based on Rim

Abstract: Schizophrenia shows high heritability and several of the genes associated with this disorder are involved in calcium (Ca2+) signalling and synaptic function. One of these is the Rab-3 interacting molecule-1 (RIM1), which has recently been associated with schizophrenia by Genome Wide Association Studies (GWAS). However, its contribution to the pathophysiology of this disorder remains unexplored. In this work, we use Drosophila mutants of the orthologue of RIM1, Rim, to model some aspects of the classical and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 126 publications
0
5
0
1
Order By: Relevance
“…Despite the ability for high-throughput behavioral screening, unexpectedly few studies have used these models to validate genes identified in human GWAS studies. In fruit flies, the voltage-gated Ca 2+ channel cacophony ( 61 ) and the adenosine triphosphate–sensitive potassium channel, ABCC9 ( 62 ), have been identified as sleep regulators following their identification in human GWAS. In addition, cross-species analysis has found that the epidermal growth factor receptor promotes sleep in C. elegans , Drosophila , and zebrafish and is associated with variation in human sleep duration and quality ( 63 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ability for high-throughput behavioral screening, unexpectedly few studies have used these models to validate genes identified in human GWAS studies. In fruit flies, the voltage-gated Ca 2+ channel cacophony ( 61 ) and the adenosine triphosphate–sensitive potassium channel, ABCC9 ( 62 ), have been identified as sleep regulators following their identification in human GWAS. In addition, cross-species analysis has found that the epidermal growth factor receptor promotes sleep in C. elegans , Drosophila , and zebrafish and is associated with variation in human sleep duration and quality ( 63 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory memory experiments were performed as previously described ( Malik et al, 2013 ; Hidalgo et al, 2021a ; Hidalgo et al, 2021b ). Groups of 20–40 (mixed sex) flies were collected about 2–5 days prior to testing and kept under LD 25°C and 70% relative humidity conditions to acclimatise to the environment they would be tested in.…”
Section: Methodsmentioning
confidence: 99%
“…The process consists of airflow passing through bubbling mineral oil or a solution of the odorant dissolved in mineral oil. The experiments were conducted under dim red light to prevent confounding visual effects on olfactory memory formation [ 99 , 100 ].…”
Section: Methodsmentioning
confidence: 99%